Cost-Effective IoT Extensions for Existing Public Coin Operated Washing Machine Towards Smarter Apartment Complexes - Setthawong*, Pisal; Triyason, Tuul; Osothsilp, Anan; Chinggungval, Titinai (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
Due to increasing urbanization in Bangkok, Thailand, it is observed that there are an increasing number of people who have moved into high-density apartment/condominium complexes. One common service that is provided at such complexes is the provision of public coin operated washing machines that allow tenants to do their laundry at a reasonable price. This has led to a new set of challenges, one of which is that the number of public coin operated washing machines is usually inadequate during peak hours, leading to long waits in queues for the tenants. The development of smart public coin operated washing machines has improved the quality of life of the tenants. This research proposes a smart public coin operated washing machine platform by extending the usefulness and convenience of existing washing machines using IoT applications. The infrastructure, the proposed application features, and the vacancy state detection of the new washing machine platform are discussed. Using the proposed platform, tenants using public coin operated washing machines can better plan when to do their laundry even during peak hours, improving their quality of life. Keywords: Internet of Things (IoT); IoT applications; washing machine extensions; smart appliances; state machines *Corresponding author: Tel.: (+66) 0-2723-2222 Ext. 2093 E-mail: pisalstt@msme.au.edu